Changes in Hall parameters after γ-irradiation (⁶⁰Со) of n-Ge - Gaidar, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Studying the γ-irradiation influence on the properties of n-type germanium (n - ‹GeAs›) within the interval of concentrations of the doping arsenic impurity 7.79×10¹³ ≤ NAs ≡ nc ≤ 6.36 × 10¹⁶cm⁻³ has shown that the initial resistivity of single crystals with concentrations NAs ≥ 5×10¹⁵ cm⁻³ remains constant within the accuracy of measurements carried out. Only in weakly doped crystals (with NAs ≈ 7.79×10¹³ cm⁻³ and less) the used doses of γ-irradiation cause appreciable reduction both in the carrier concentration nc and their mobility μ.